Effect of Flow of Information on Student Engagement in Public Universities in Nairobi City County, Kenya - Maina, Cecilia; Mberia, Hellen (International Journal of Communication and Public Relation, 2023)
Purpose: The aim of the study was to examine the effect of flow of information on student engagement in public universities in Kenya Methodology: The study used a mixed research design with both qualitative and quantitative research methods. The target population was all the students in the public universities within Nairobi City County. A sample of 384 students was drawn from the five public chartered universities' main campuses, using a combination of various probability sampling techniques including stratified, simple random sampling and systematic sampling. The academic registrar in each of the university was sampled for interviews using purposive sampling. The research instruments for this study were self-administered questionnaires for students and semi-structured interviews for the registrars. Quantitative data was analyzed using the SPSS software and the inferential statistics used were descriptive, correlation, regression and ANOVA analysis. Qualitative data was analyzed for themes, and triangulation of both quantitative and qualitative data done. Findings: Lateral communication (student-student) is well established in public universities and students easily share information with one another. Downward (management-student) and upward (student-management) communication was however wanting with students feeling that they are not consulted enough even on issues that directly affect them. This is despite having representation by their student representatives at various levels of the decision-making processes in the university. Students also stated that they could not freely communicate their opinions to the management despite being provided with channels to do so. Unique Contribution to Theory, Practice and Policy: The study was guided by the Organizational Information Theory (OIT). The study therefore recommended that better ways of engaging students directly, such as meetings could also be considered instead of relying on student leadership representation alone. Public universities should establish clear and comprehensive communication policies that outline the channels, frequency, and modes of communication between the institution, faculty, and students.